A study on service quality towards free zone’s tenants at Port of Tanjung Pelepas / Sufiah Hayati Abd Rahim - Abd Rahim, Sufiah Hayati (2009)
The purposes of this study are to find out that either the services given meet the tenants’ needs and wants or not and the most important factor that the tenants put it as the first reason they having a business with Port of Tanjung Pelepas. This study, thus have the following objectives :